Incidental archaeologists : French officers and the rediscovery of Roman North Africa - Effros, Bonnie, 1965- (Cornell University Press, 2018)
"From 1830, the Roman ruins of North Africa intrigued invading French military officers and became key to the colonial narrative justifying French settlement of North Africa"--